'To become again our brethren': desertion and community during the American Revolutionary War, 1775–83. Issue 248 (29th March 2017) - Chandler, Jonathan
Abstract: Desertion from active military service has always been a contentious action, especially in times of war. Deserters in the eighteenth century were routinely castigated as poor patriots or traitorous subjects. Recently, scholars have begun to analyse in greater depth how and why desertions occurred, and have demonstrated that political considerations were less important than issues of identity and interest. However, in the context of the American Revolutionary War, historians have focused on the relationship between deserters and the military, arguing that soldiers who left their posts were less integrated into the camp community. This article suggests that the act of desertion was often more than a protest against conditions or discipline, but instead was shaped by a deserter's connections with civil society rather than the military community.